2018
DOI: 10.1016/j.jhg.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Transportation and regional inequality: the impact of railways in the Nordic countries, 1860–1960

Abstract: Before industrialisation, the Nordic countries (Denmark, Finland, Norway and Sweden) were part of Europe's poor periphery, but over the last century these countries have become some of the richest in the world. This article analyses the origins of Nordic growth from the late-nineteenth century, focusing on a previously neglected topic: the role of transportation. We argue that transportation, and most notably large investments in railways, played a key role in Nordic industrialisation. Railways made the exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 4 publications
1
21
0
1
Order By: Relevance
“…However, due to fast development of the road and the growth in transportations, the building required re-construction [7]. In 1868 I.V.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to fast development of the road and the growth in transportations, the building required re-construction [7]. In 1868 I.V.…”
Section: Resultsmentioning
confidence: 99%
“…No studies devoted to the station's architectural form shaping were found among foreign works. Nevertheless, the general issues of Art Nouveau, railway infrastructure development, construction experience and railway stations' adaptation prospects are addressed in a variety of works and are of significant interest [7,26,28,41,43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main advantage of this paper is the construction of a spatial database of the railway network for the period 1847-1914. Although many researchers have discussed the impacts of railway construction on socio-economic processes in the past (Kerstin et al, 2018;Murzyn-Kupisz & Gwosdz, 2011), the original data were usually not shared with readers. For times when we know that historical processes influenced the current state of countries and regions (Grosfeld & Zhuravskaya, 2015) of which railway systems are a very good example (Król & Taczanowski, 2016;Taczanowski, 2012) or impacted the current ecosystem functioning (Munteanu et al, 2017), historical geography is still rarely 'data rich'.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, water supplying PPP projects should improve water quality by bringing the private technological advantage. Compared with other types of transport, railways have the advantage of reducing traffic costs in medium-distance transportation and promoting substantial growth in interregional trade (Enflo, Alvarez-Palau, & Marti-Henneberg, 2018;Yi & Kim, 2018). Through the PPPs, railways projects can get a lower construction and operation costs as well as high management efficiency, which can expand the traffic costs advantage (Gangwar & Raghuram, 2015).…”
Section: Weighting the Indicator System Of The Ssces For Pppsmentioning
confidence: 99%